Terlambatnya Proses Pendinginan Muatan Gas Polymer Grade Propylene di Kapal LPG/C Coral Millepora - Mavji Mochammad Fauzi; Akhmad Ndori (Dinamika Bahari, 2021)
The LPG Carrier is one of the ships that carries liquid gas cargoes below -48o C. The LPG Carrier has facilities in the form of a reliquefaction plant that uses seawater as a coolant for gas cargo. Therefore, the reliquefaction plant has an important role in the smooth loading and unloading process. If one of the reliquefaction plant particles is damaged, of course the cooling process of the polymer grade propylene gas load will be hampered. The purpose of this study is to describe the problem in the cooling process of polymer grade propylene load. The authors conducted research using a qualitative descriptive method through an interview approach, direct observation of the object of research, and supported by paper-based documents or photos. Based on the results of the study, it was found that the causes of delays in the cooling process of polymer grade propylene gas cargo, namely the influence of weather, sea water content, clogged sea water filters, clogged condenser tubes, and condenser shell tube leaks.